Zarządzanie krajobrazem jako aspekt zarządzania środowiskiem - Mizgajski, Andrzej (My University, 2008)
The purpose of this paper is to show landscape management as a field of research and to present application activities associated with the reference of landscape assets. this problem was presented against the background of the analysis of conceptual scopes of related terms used in environmental sciences. The use of ecosystems services (landscape services) concept, which is based on the quantification of material and non- material benefits for the society resulting from a particular formation of natural features, provides promising prospects for landscape management. The emerging field of research can be a significant factor for the integration of the areas of concern of physical geography and economic geography.
Landscape management as an aspect of environmental management
Keywords: badania krajobrazu; świadczenia ekosystemów; geografia fizyczna; landscape research; ecosystems services; physical geography